2019
DOI: 10.33881/2027-1786.rip.11301
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de Bullying y Cyberbullying en Latinoamérica: una revisión

Abstract: El objetivo de este trabajo consiste en realizar una revisión sistemática de las investigaciones que aportan porcentajes de víctimas y agresores de bullying y cyberbullying en Latinoamérica (2005-2018). Con esta finalidad se utilizan las principales bases de datos(Scopus, WebOfScience, ERIC). Se han encontrado 51 estudios, 35 sobre bullying,10 de cyberbullying y 6 aportan información de ambas modalidades de acoso. Losresultados evidencian una alta prevalencia de bullying y, aunque en menor medida tambiénde cyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
40

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 28 publications
1
18
1
40
Order By: Relevance
“…Physical aggression includes hitting, kicking, punching, taking or damaging belongings; verbal aggression comprises teasing, taunting or threatening; relational/social aggression or social exclusion includes rumors or exclusion with the intention to damage self-esteem and/or social status [6]. Cyberbullying consists of using Information and Communication Technologies (ICTs; email, instant messaging or "chat", websites or blogs, online video games and mobile phones) to exercise psychological abuse [8].…”
Section: Introductionmentioning
confidence: 99%
“…Physical aggression includes hitting, kicking, punching, taking or damaging belongings; verbal aggression comprises teasing, taunting or threatening; relational/social aggression or social exclusion includes rumors or exclusion with the intention to damage self-esteem and/or social status [6]. Cyberbullying consists of using Information and Communication Technologies (ICTs; email, instant messaging or "chat", websites or blogs, online video games and mobile phones) to exercise psychological abuse [8].…”
Section: Introductionmentioning
confidence: 99%
“…Del mismo modo, la evidencia empírica en América Latina arroja que la prevalencia del cyberbullying es relevante (Garaigordobil, Mollo-Torrico, & Larrain, 2018). Se presentan altos índices de ciberacoso en países como México (Vega-Cauich, 2019), Colombia (Herrera-López, Romera, & Ortega-Ruiz, 2018), Chile (Menay-López & de la Fuente-Mella, 2014) y Argentina (Lanzillotti & Korman, 2014).…”
Section: Ciberacosounclassified
“…Bullying is a specific form of school violence, where one or more attackers intentionally cause pain, harass, and repeatedly subject another classmate. When we talk about face-to-face or presential bullying, we refer to: (1) the existence of a defenseless victim, harassed by one or more assailants; (2) who carry out different types of aggressive face-to-face behavior toward the victim, aggressive physical behaviors aimed at the victim's body or property (hitting, pushing, breaking, hiding, or stealing the victim's objects…), aggressive verbal behaviors (giving nicknames, insulting, saying unpleasant things about the victim…), behaviors of social exclusion (not letting the victim participate, excluding, telling lies, or spreading false rumors about the victim so she will be rejected by others…), aggressive psychological behaviors (aimed at undermining the victim's self-esteem, creating insecurity and fear: threatening, blackmailing, laughing at him, humiliating him…; although it should be borne in mind that all types or forms of bullying have a psychological component); (3) it is maintained physical and mental violence; (4) the aggressors intend to harm, they are purposely cruel to make the victim suffer; (5) there is usually an inequality of power between the victim and the aggressors (physical, verbal, or psychological inequality); (6) these aggressive behaviors are repeated frequently, there is a dominion-submission relationship between the aggressor or aggressors and the victim that is maintained over time; and (7) in addition, the aggression not only produces pain when it occurs, as the victim feels sustained pain and anguish due to expectations of future attacks, aggressions, or humiliation that he or she anticipates suffering (Garaigordobil, 2017 ).…”
Section: Introduction: Conceptualization Prevalence and Prevention Omentioning
confidence: 99%
“…What behaviors do cyberaggressors perform? A review of the behaviors identified by numerous authors (Aftab, 2010 ; Kowalski et al, 2010 ; Tokunaga, 2010 ; Garaigordobil, 2013 , 2015 ) identifies the following: (1) sending insulting, threatening, disparaging, or intimidating messages through mobiles or e-mail (ugly, fat, everybody hates you, you should die, be careful; we're going to beat you up…); (2) making anonymous phone calls to frighten the victim; and/or making threatening, intimidating, insulting, or disparaging calls…; (3) manipulating photographs to ridicule or create a false image of the victim, which the aggressors distribute by mobile phone or internet; (4) excluding, isolating the victim from social networks (Facebook, WhatsApp, Instagram…); (5) stealing the victim's password, and impersonating her identity (for example, sending aggressive messages to the victim's contacts to anger them; violating the victim's privacy, changing her password to prevent her access to her email account…); (6) provoking the victim in chats, online games, virtual communities… to achieve her violent reaction, which they then denounce to the Service Manager so he will impede her access to that service; (7) creating a false profile of the victim and, for example, making explicit offers of sexual contacts, giving the victim's mobile phone as the contact…; (8) signing up on some websites with the victim's email address so he will continuously receive emails and SPAM…; (9) disseminating lies about the victim to harm her (false rumors, slander…); (10) disseminating secret or embarrassing information about the victim, for example, concerning his orientation to his sexual identity; (11) denigrating or badmouthing the victim on a website, a personal blog, a social network…; (12) making surveys to disparage the victim, for example, choosing her as the ugliest, the least intelligent, the fattest… and giving her the points or votes, which go to her email; (13) beating up or placing the victim in a humiliating situation, recording it on the mobile, and broadcasting the video via mobile or uploading it to YouTube (happy slapping)… (Garaigordobil, 2017 ).…”
Section: Introduction: Conceptualization Prevalence and Prevention Omentioning
confidence: 99%